2015
DOI: 10.1007/s10461-014-0984-8
|View full text |Cite
|
Sign up to set email alerts
|

mHealth Technology as a Persuasive Tool for Treatment, Care and Management of Persons Living with HIV

Abstract: Mobile health (mHealth) technology can be a valuable tool in the management of chronic illnesses, including HIV. Qualitative research methods were used to identify the desired content and features of a mobile app for meeting and improving the healthcare needs of persons living with HIV (PLWH). We conducted six focus group sessions with 50 English-or Spanish-speaking PLWH in New York City. To inform data analysis and to illustrate how mHealth technology can be used as a persuasive strategy for improving the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
90
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 35 publications
6
90
0
Order By: Relevance
“…Our study findings confirmed results of prior studies where the storing and tracking of lab results and medication and appointment reminders were identified as desirable app functionalities for PLWH [17][18][19][20][21]. In our study, access to blood test results has been imagined and anticipated as being an important function by both patients and clinicians.…”
Section: Medical Functionalitiessupporting
confidence: 88%
See 4 more Smart Citations
“…Our study findings confirmed results of prior studies where the storing and tracking of lab results and medication and appointment reminders were identified as desirable app functionalities for PLWH [17][18][19][20][21]. In our study, access to blood test results has been imagined and anticipated as being an important function by both patients and clinicians.…”
Section: Medical Functionalitiessupporting
confidence: 88%
“…Along with the results of other studies, our participants suggested that an mHealth platform could facilitate a peer-support network [17][18][19][20]32]. Additionally, our participants imagined an app supporting them while travelling internationally (e.g.…”
Section: Social Functionalitiessupporting
confidence: 73%
See 3 more Smart Citations